Pengaruh Pembelajaran Berbasis Proyek Dalam Kurikulum Merdeka Terhadap Hasil Belajar Siswa Pada Mata Pelajaran PAI - Raito Raito; Anisa Siti Aqila (STAI Al-Musaddadiyah Garut, 2026)
Creating a conducive and well-maintained school environment to support learning and foster an environmentally conscious character. Observations at Al-Hikmah Tarogong Kaler Junior High School, Garut, showed that students did not fully understand the concept of environmental conservation, were inconsistent in their environmental stewardship, and lacked skills in environmental maintenance practices. This situation demonstrates the need for an innovative learning model that not only enhances knowledge but also fosters active and independent student attitudes and skills. Previous research has shown that project-based learning effectively improves learning outcomes focused on Mathematics. The novelty of this research lies in the application of project-based learning to Islamic Religious Education (PAI) subjects within the Independent Curriculum, emphasizing cognitive, affective, and psychomotor aspects. The application of project-based learning with the theme